Arctic cinema: from horror through dramas and thrillers To Action movies and fiction (Part I) - I. S. Zonn; И. С. Зонн (The Centre of Regional Research, 2023)
The article considers a number of genres of Arctic films in the world cinema. Among them, some of the most common are horror films (horror), thrillers (part I), dramas, science fiction and action films (part II). The socio-political climate of the times determined the evolution of genres and influenced their semantic content and structure. Their formation and production flow has a calendar milestone. In the second half of the twentieth century, after the end of the Great Patriotic War, a cold war began between two blocs of states with different socio-economic systems led by the USSR and the USA. It was she who strengthened the militaristic role of the Arctic not only in the military-industrial sphere, but also in the cinematographic one. Hollywood, as part of the political and ideological machine of the United States, immediately responded with its films. The screen was politicized in the general range of Cold War sentiments. Conducting atomic tests, the appearance of the atomic bomb in the USA in 1945 and in the USSR in 1949, “flying saucers” from space, noted in 1947, brought to life horror films, science fiction and drama. The heroes of the films were monsters that descended to earth from outer space or rose from the depths of the ocean, all kinds of mechanical and biological monsters awakened by nuclear tests. In parallel, western cinema constructed models of anti-Soviet orientation. The purpose of the films was to amuse and captivate the viewer into an illusory world and at the same time, to shock, amaze, terrify and excite him with scientific or pseudoscientific fiction. This goal remains the main one for most fantastic horror and thrillers. Some of them preached violence, cruelty, conflict, degradation of the human personality. Aggressiveness, programmed in the person himself, is increasingly, manifested in Arctic thrillers and action film. В статье рассмотрен ряд жанров арктических фильмов в мировом кинематографе. Среди них одни из наиболее распространенных — фильмы ужасов (хоррор), драмы (I часть), ...